ASSESSMENT OF THE CONCENTRATIONS AND HUMAN EXPOSURE TO HEAVY METALS IN BATHING SOAPS IN NIGERIA - Oviri, Victory I.; Tesi, Godswill O.; Emoyan, Onoriode O. (FUDMA JOURNAL OF SCIENCES, 2024)
The presence of heavy metals in consumer products, particularly in personal care items like soaps, poses potential health risks to consumers. This study aimed to determine the concentrations and risks of Pb, Ni, Zn, Co, Cd and Cr in commonly used bathing soaps available in the Nigerian market. A total of seventeen bathing soaps comprising of medicated, moisturizing, toilet and skin whitening soaps were obtained for this study. Analytical procedures under satisfactory conditions were harnessed to determine the various concentrations and the results revealed varying concentrations of Pb (0.08 to 0.39 mg/kg), Ni (0.05 to 0.33 mg/kg), Zn (0.10 to 6.42 mg/kg), Co (0.04 to 1.93 mg/kg), Cd (0.02 to 0.09 mg/kg), and Cr (0.01 to 0.19 mg/kg) across the different soap categories. The systemic exposure dosage (SED) values for these metals obtained from the use of these bathing soaps were below their respective provisional tolerable daily intake or recommended daily intake values. The margin of safety (MoS) values obtained were greater than 100 which indicated that the concentrations of the metals in these soaps do not present considerable risk to the users. The findings underscore the importance of regular monitoring and regulation of heavy metal content in consumer products, particularly personal care items like soaps. As prolonged exposure to these metals, even in trace amounts, may have adverse effects on human’s health and long-term toxicity. Therefore, stringent quality control measures and regulatory standards are imperative to safeguard public health and ensure the safety of consumers in Nigeria.